Quantitative feedback theory-based multi-variable robust control for soil quality improvement in a drip irrigated field. (March 2023) - Chakravarty, Sandipan Prasad; Roy, Prasanta
Abstract: This article presents the control of Soil moisture, Nitrogen, and Salt content in soil using a robust control technique to maintain a desired quality of soil in a drip irrigated field. The control of this multi-variable system is accomplished by adopting two possible control structures namely (i) a decentralized controller backed by a feed-forward controller (ii) a diagonal centralized de-coupler along with a diagonal controller. The controllers are designed using quantitative feedback theory. The efficacy of the proposed techniques is validated through numerical simulations. A comparative study among the two methods reveals that the former performs better than the later. Another comparative study shows that the proposed controller outperforms some of the reported works. Highlights: Control of Soil moisture, Nitrogen and Salt content in a drip irrigated field. A 3 × 3 uncertain model is derived from physical laws and practical data. De-centralized QFT along with feed-forward controllers is proposed. Centralized decoupler with diagonal QFT based controllers is proposed.